The potential of drones in Agricultural Sustainability : A Systematic Review - Mossmann, Cléria Regina do Nascimento; Binotto , Erlaine (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – Analyze the strategic role of drones in agriculture, highlighting their productive efficiency and contribution to environmental, social and economic sustainability. Methodology – Theoretical approach based on a systematic review, exploring technological advances, challenges and benefits of using drones in precision agriculture (PA). Originality/Relevance –The study fills the gap on the integration of drones and emerging technologies in agricultural sustainability, advancing research in AP, innovation and productive-environmental impact. Results – Drones improve agricultural monitoring, optimize the application of inputs and reduce operational costs, while promoting more sustainable agricultural practices. Theoretical/Methodological Contributions – The main contributions include an updated overview of the technology and its agricultural application. Social and Environmental Contributions – Socially and environmentally, the contribution of drones to more sustainable agricultural practices stands out.